Seizures arising from the inferior parietal lobule can show ictal semiology of the second sensory seizure (SII seizure). Issue 3 (1st March 2003) - Yamamoto, J; Ikeda, A; Matsuhashi, M; Satow, T; Takayama, M; Ohara, S; Matsumoto, R; Mikuni, N; Takahashi, J; Miyamoto, S; Taki, W; Hashimoto, N; et al.
Abstract : A 52 year old right handed man presented with medically intractable partial seizures consisting of numbness on the left upper back spreading to the left upper as well as lower limbs. Head computed tomography and magnetic resonance imaging showed a round calcified lesion in the depth of the superior ramus of the right sylvian fissure. Ictal electrocorticographic recording with chronically implanted subdural electrodes showed low voltage fast activities starting exclusively from an electrode located on the right inferior parietal lobule. No apparent ictal activities were observed from the depth electrodes inserted in the parietal operculum. Somatosensory evoked potentials of 75 ms to 145 ms latency were recorded from the ictal onset zone, which was 2 cm caudal to the perisylvian area corresponding to the second somatosensory area. Seizures arising from the inferior parietal lobule including the angular and supuramarginal gyri can produce partial seizures whose ictal semiology and scalp electroencephalography are indistinguishable from the ones originating from the second somatosensory area.